Penjatuhan Sanksi Hukuman Pidana Maksimal bagi Tindak Pidana Korupsi yang Dilakukan Masa Pandemi - Edshafa Muharatulloh (CV. Ulil Albab Corp, 2023)
The crime of corruption is a problem that has a global nature, no longer a problem that is regional in nature, even regional, in terms of corruption, it can cause the stability and security of the state and society to be fragile, even during the Covid-19 pandemic which resulted in the Indonesian state being in a state of which is troubling from an economic and health to social perspective, but there are some individuals who are still looking for opportunities to benefit by means of corruption. Funds that should be given to help the community are instead used by taking some for their benefit, one of the cases, namely the case of Juliari P Batubara, who carried out gratuities which causes a loss in the Social Assistance Fund. regarding the case of Juliari P Batubara in gratuities in procuring social assistance in the context of handling Covid-19. The purpose of this study is the decision handed down by the judge on criminal penalties for corruption during the Covid-19 pandemic. This research is a normative research with a conceptual approach. Types of legal materials consist of primary legal materials, secondary legal materials, and tertiary legal materials. The legal material collection technique used is a literature study which is then processed using a legal material selection system in data processing techniques. Based on Article 2 paragraph (2) of Law Number 20 of 2001 regarding the application of capital punishment in the phrase